Etos Kerja Guru Berbasis Spiritualitas Islam: Antara Kesederhanaan, Kesejahteraan, dan Kebijakan Pendidikan - Amalia Nurusya`bani; Dwi Rahmawati (Universitas Muhammadiyah Magelang, 2026)
The role of Islamic spiritual values ”‹”‹in shaping the work ethic of teachers, particularly Islamic Religious Education (PAI) teachers, in facing the challenges of welfare, professionalism, and educational policy is not yet fully equitable. This study uses a descriptive qualitative approach with a library study method that aims to understand and interpret social phenomena through the analysis of various relevant literature sources. Data collection was conducted through documentation studies, namely by reviewing books, scientific journal articles, research reports, and academic documents related to the research topic. This study found that zuhud is not an attitude of absolute estrangement from the world, but rather placing the world in a balanced position so that it does not become the primary goal in life. Meanwhile, qana'ah does not mean helpless resignation, but rather accepting enough of the sustenance available while still actively and critically striving. The integration of these two values ”‹”‹in the teacher's personality creates a patient, resilient, and dignified character, while also being able to be critical of systemic inequality. This study emphasizes that educational policies must be built on the basis of structural justice as well as spiritual moral values, so as not only to demand teacher devotion, but also to fulfill their basic rights. Spirituality should be a powerful force for change, not a justification for an unequal system. Therefore, this article recommends a synergy between spiritual development, character building, and the design of fair, sustainable, and teacher-empowering Islamic education policies.